Colégio Pedro II: A study on legislation and applied indicators (Research, Society and Development, 2021)
Created in 1837, Colégio Pedro II has its area of ​​activity from Early Childhood Education to the Stricto Senso Graduate Program. Law 11,892 of 2008 created the Federal Institutes and had its wording updated by Law 12,677 of 2012, including Colégio Pedro II in the Federal Education, Scientific, Professional and Technological Network. Law         12.677/12 maintained the traditional name “Colégio Pedro II”, however, equating it to the condition of Federal Institute of Education, Science and Technology. The article mainly addresses the legal aspects of this assimilation, explaining legal concepts and commenting on the main articles of the relevant legislation, in addition to analyzing relevant economic and social indicators of the institution.